(untitled) (Clinics, 2005)
PURPOSE: To evaluate the effects of red blood cell transfusion in patients with SIRS/sepsis who presented hemoglobin levels under 9.0 g/dL at intensive care unit admission, using two parameters of organ perfusion: mixed venous oxygen saturation and serum lactate levels. METHODS: All patients admitted to the intensive care unit with SIRS/sepsis, as defined by Consensus Conference in 1992, and hemoglobin levels under 9.0 g/dL were included. Hemoglobin levels, mixed venous oxygen saturation, and lactate levels were collected before red blood cell transfusion (pre-T) and up to 1 hour after transfusion (post-T). These variables were analyzed through a paired t test, and results were considered significant if P < .05. RESULTS: Twenty-nine patients (17 male, 12 female) with ages of 61.9 ± 15.1 (mean ± SD) years (range, 21-85 years) and a mean APACHE II score of 12.5 ± 3.75 (7-21) were transfused with a mean of 1.41 packed red cell units. A significant increase in hemoglobin levels was reached by blood transfusion, from 8.14 ± 0.64 g/dL (pre-T) to 9.4 ± 0.33 g/dL (post-T), with P